A technique for open chest selective aortic arch perfusion. Issue 6 (June 2021) - Abdou, Hossam; Madurska, Marta J.; Edwards, Joseph; Patel, Neerav; Richmond, Michael J.; Galvagno, Samuel; Kundi, Rishi; DuBose, Joseph J.; Scalea, Thomas M.; Morrison, Jonathan J.
Abstract : Supplemental digital content is available in the text.